Understanding the defense-related mechanism during the wheat’s interaction with fungal pathogens - A. SETHI, VINOD K. MISHRA, RAMESH CHAND, ARUN K. JOSHI, AUNDY KUMAR and SHREE P. PANDEY, RANABIR SAHU, PRITHA KUNDU, MURALI SHARAFF, MAITREE PRADHAN (Indian Phytopathology, 2016)
Wheat is one of the most important cereal crops of the world but its production faces several challenges from fungal pathogens such as spot blotch and rust. While the devastating effects of rust is already known, spot blotch disease is gaining an epidemic status simultaneously. Spot blotch of wheat, caused by Bipolaris sorokiniana, results in an average 17% loss in yield, which may rise to 100% in favorable conditions. Little is known about the molecular responses, including phytohormone mediated defense signaling of wheat against pathogens like Bipolaris sorokiniana. In the present study, we have performed the molecular characterization of wheat spot blotch interaction from the perspective of defense signaling. Our integrative biology approach involved time-dependent studies in wheat populations, including gene expression studies and analytical chemistry based evaluation of signaling and defense molecules. We carried out experiments to decipher reprogramming of expression of defense-signaling pathways including salicylic acid (SA), and jasmonic acid (JA). Our results demonstrate a central role of SA and phenylpropanoid pathways in defense associated response against spot blotch in wheat. On the contrary, rust pathogen may be able to antagonize SA against JA signaling, thus rendering wheat susceptible to its infection.